2022
DOI: 10.1186/s12888-022-04241-2
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perspectives of the effects of a group-based therapeutic patient education program for bipolar disorder: a qualitative analysis

Abstract: Background Few qualitative studies have explored the impact of group-based psychoeducation programs from the perspective of patients with bipolar disorder, and no studies to date have examined the effects of such programs on patients’ personal recovery. The aim of this study was to explore the effects of a group therapeutic education program on the personal recovery of people with bipolar disorder and its determinants. Methods Three professionals c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Thus, all our results are in favor of the action of TPE in the recovery process according to Leamy and her colleagues. Another qualitative study carried out in our department in the same time regarding patients participating in TPE programs confirmed the benefits of the TPE program on the personal recovery of people with bipolar disorder and indicated that it improved all dimensions of recovery in the CHIME model [ 25 ]. Duval and her colleagues also stated that sharing experiences among peers promotes knowledge of the illness, a sense of being understood by others, and a sense of belonging to a group.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, all our results are in favor of the action of TPE in the recovery process according to Leamy and her colleagues. Another qualitative study carried out in our department in the same time regarding patients participating in TPE programs confirmed the benefits of the TPE program on the personal recovery of people with bipolar disorder and indicated that it improved all dimensions of recovery in the CHIME model [ 25 ]. Duval and her colleagues also stated that sharing experiences among peers promotes knowledge of the illness, a sense of being understood by others, and a sense of belonging to a group.…”
Section: Discussionmentioning
confidence: 84%
“…The participants had all participated in psychoeducation as part of the standard treatment at the clinic. Psychoeducation as an add-on treatment has several benefits, including reducing relapse rate, improving treatment adherence, improving social functioning and promoting healthy habits in patients (Duval et al 2022 ; Bond and Anderson 2015 ). We found in our study that age and time living with a diagnosis of BD had improved coping strategies regarding sexuality and BD.…”
Section: Discussionmentioning
confidence: 99%
“…For some individuals, recovery is the ability to live a fulfilling and productive life despite a disability. For others, recovery implies the reduction or complete remission of symptoms [ 14 ].” The concept of recovery is applicable to many individuals with mental illnesses other than schizophrenia [ [15] , [16] , [17] , [18] ]. Recovery is broadly classified into clinical recovery (i.e., the objective improvement in symptoms and functioning) and personal recovery (i.e., the restoration of self-worth and meaningful life) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%